1997
DOI: 10.1073/pnas.94.26.14787
|View full text |Cite
|
Sign up to set email alerts
|

A new mechanism of sound generation in songbirds

Abstract: Our current understanding of the soundgenerating mechanism in the songbird vocal organ, the syrinx, is based on indirect evidence and theoretical treatments. The classical avian model of sound production postulates that the medial tympaniform membranes (MTM) are the principal sound generators. We tested the role of the MTM in sound generation and studied the songbird syrinx more directly by filming it endoscopically. After we surgically incapacitated the MTM as a vibratory source, zebra finches and cardinals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
121
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 147 publications
(124 citation statements)
references
References 24 publications
(22 reference statements)
2
121
0
Order By: Relevance
“…The precise rotational movement of the third bronchial semi-ring, which is involved in controlling the position of the lateral labium is still not su¤ciently understood (e.g. Chamberlain et al 1968;Goller & Larsen 1997), and the biomechanical mechanisms responsible for moving the medial labium have not been described. The muscles involved in this process of controlling the syringeal aperture have, however, been identi¢ed.…”
Section: (B) Controlling Syringeal Aperturementioning
confidence: 99%
See 1 more Smart Citation
“…The precise rotational movement of the third bronchial semi-ring, which is involved in controlling the position of the lateral labium is still not su¤ciently understood (e.g. Chamberlain et al 1968;Goller & Larsen 1997), and the biomechanical mechanisms responsible for moving the medial labium have not been described. The muscles involved in this process of controlling the syringeal aperture have, however, been identi¢ed.…”
Section: (B) Controlling Syringeal Aperturementioning
confidence: 99%
“…Each bronchus contains a pair of sound-generating medial and lateral labia. These can be adducted into the bronchial lumen and function as valves to regulate syringeal air£ow by restricting or closing the lumen of the ipsilateral side of the syrinx (Goller & Larsen 1997). The syringeal aperture and other aspects of syringeal con¢guration are controlled by half a dozen pairs of muscles (four intrinsic and two extrinsic) that envelop the syrinx (King 1989)(¢gure 3).…”
Section: The Vocal Organ (A) Structure and Innervationmentioning
confidence: 99%
“…During phonation, air is pushed through the primary bronchi towards the mouth, while bronchial and tracheal membranes are pushed inwards by pressure in the interclavicular air sac. Endoscopic observations have shown that during phonation in songbirds, the syrinx deforms so that the medial and lateral labia ( just distal to the medial membranes of the bronchi) are pushed inwards forming a`vocal slit' which is analogous to the laryngeal vocal slit in mammals (Goller & Larsen 1998). The £ow of air sets the labia into oscillation with a fundamental frequency corresponding to that of the recorded sound.…”
Section: (C) Vocalization In Birdsmentioning
confidence: 99%
“…Recent studies have not, however, supported this type of mechanism (Goller & Larsen 1997, 1998Ballintijn & Ten Cate 1998) in pigeons (a`non-songbird') and songbirds. Alternatively, voiced sounds are produced by a £ow-induced vibration of membranes (in non-songbirds; Goller & Larsen 1997) or labia and membranes (in songbirds; Goller & Larsen 1998) in the syrinx (the principal vocal organ around the junction of trachea and primary bronchi). During phonation, air is pushed through the primary bronchi towards the mouth, while bronchial and tracheal membranes are pushed inwards by pressure in the interclavicular air sac.…”
Section: (C) Vocalization In Birdsmentioning
confidence: 99%
“…It has been reported that the LTM is the main sound generator in pigeons (4). Furthermore, Goller and Larsen (11) suggested that the labia play an important role as principal sound generators in the songbirds. Riede and Goller (12) also reported that laterally positioned labia are passively set into vibration, thus interrupting a passing air stream.…”
Section: Introductionmentioning
confidence: 99%